Comprehensive Toxic Plants-Phytotoxins Database and Its Application in Assessing Aquatic Micropollution Potential - Günthardt, Barbara F; Hollender, Juliane; Hungerbühler, Konrad; Scheringer, Martin; Bucheli, Thomas D (Journal of agricultural and food chemistry, 2018)
The production of toxic plant secondary metabolites (phytotoxins) for defense is a widespread phenomenon in the plant kingdom and is even present in agricultural crops. These phytotoxins may have similar characteristics to anthropogenic micropollutants in terms of persistence and toxicity. However, they are only rarely included in environmental risk assessments, partly because a systematic overview of phytotoxins is missing. Here, we present a newly developed, freely available database, Toxic Plants-PhytoToxins (TPPT), containing 1586 phytotoxins of potential ecotoxicological relevance in Central Europe linked to 844 plant species. Our database summarizes phytotoxin patterns in plant species and provides detailed biological and chemical information as well as in silico estimated properties. Using the database, we evaluated phytotoxins regarding occurrence, approximated from the frequencies of Swiss plant species; environmental behavior based on aquatic persistence and mobility; and toxicity. The assessment showed that over 34% of all phytotoxins are potential aquatic micropollutants and should be included in environmental investigations.
Keywords: chemické látky znečišťující vodu; poisonous plants; biologické toxiny; Plants, Toxic; databáze faktografické; Water Pollutants, Chemical; jedovaté rostliny; risk assessment; Toxins, Biological; natural toxins; aquatic pollution; Databases, Factual; invasive species